Life-history traits and intra-cohort divergence of clearhead icefish (Protosalanx chinensis), indicating cannibalism increased fitness - Fujiang Tang; Wei Liu; Jilong Wang; James Henne (PeerJ, 2020)
Cannibalism is considered one of the causes of intra-cohort size divergence in fish and is usually believed to result in increased fitness in terms of survival and reproduction, but direct evidence of this is lacking. Population demographics of the clearhead icefish (Protosalanx chinensis) from Lake Xingkai (Khanka) were investigated for one year. Size-frequencies exhibited a bimodal distribution from July through January, where the population diverged into an upper and a lower modal group based on size. Stomach content analysis confirmed the occurrence of cannibalism, where fish belonging to the larger, upper modal group preyed upon those of the smaller, lower modal group. We found P. chinensis does not spawn until all of the oocytes have reached maturity and then a single spawning event occurs although the oocytes may develope asynchronously in the ovary. Upper modal group females matured slightly earlier than those of the lower modal group, and reproductive investment was considerably greater in the upper modal group than the lower modal group. The lower modal males made up the majority of the population after the spawning period, which meant they may have few opportunities to participate in reproduction. Therefore, piscivory and cannibalism of P. chinensis appears to have increased fitness of the fish belonging to the upper modal group and greatly reduced the fitness of those belonging to the lower modal group.